Relationship between self-regulated learning and academic procrastination - Yap, Li San; Roslan, Samsilah; Sabouripour, Fatemeh (Science Publications, 2016)
This study aims to investigate the relationship between the components of motivation in self-regulated learning as well as the components of learning strategies in self-regulated learning and academic procrastination. Academic procrastination creates problems for undergraduates such as stress and poor academic performance which should be investigated as a serious issue in the educational context. The participants in this study included 100 undergraduates in Universiti Putra Malaysia. The result of a Pearson correlation analysis revealed intrinsic goal orientation, task values, rehearsal, elaboration, meta cognitive self-regulation, resource management strategies, organisation and critical thinking as self-regulated learning components that have significant negative correlations with academic procrastination. In addition, anxiety was found to have a significant positive correlation with academic procrastination. Extrinsic goal orientation and control of learning beliefs were not significantly correlated to academic procrastination. The findings suggested that in order to cope with academic procrastination, an academic procrastinator might consider being a self-regulated learner as most of the components of self-regulated learning indicated a strong relationship with academic procrastination that can be encouraged in order to improve those lacking components of self-regulated learning. Also, to help undergraduates to improve on the components of self-regulated learning that they lack, strategies can be planned by educators to deal with academic procrastination and to increase academic performance.